Calcium-zinc stabilizer, preparation method and application
By adding concave and convex rod soil and graphene oxide to the calcium and zinc stabilizer, the problem of insufficient thermal stability performance of existing calcium and zinc stabilizers in polyvinyl chloride is solved, and the efficient thermal stability and processing stability of polyvinyl chloride is achieved. .
Patent Information
- Application Number
- CN202411530235.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
When used in polyvinyl chloride, the thermal stability performance of existing calcium and zinc stabilizers is limited, especially in the heated state during processing, the stability is poor.
By adding concave and convex rod soil and graphene oxide to the calcium and zinc stabilizer, the rod-like structure of concave and convex rod soil and the porous structure of graphene oxide can be used to improve the movement speed of calcium and zinc ions, so that they can be quickly distributed in polyvinyl chloride And capture free radicals.
It significantly improves the thermal stability performance of polyvinyl chloride, extends its discoloration time in static and dynamic thermal stability tests, and improves the stability and performance during processing.
Smart Images

Figure BDA0005110299040000071 
Figure BDA0005110299040000111 
Figure BDA0005110299040000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of calcium zinc stabilizers, and in particular to a calcium zinc stabilizer, a preparation method and an application thereof. Background Art
[0002] Polyvinyl chloride is a synthetic plastic that is used in numerous applications due to its excellent properties such as flame retardancy, chemical resistance, and cost-effectiveness.
[0003] However, the thermal stability of polyvinyl chloride is poor. At high temperatures, polyvinyl chloride will decompose to produce hydrogen chloride, which seriously affects its performance. Currently, adding thermal oxygen stabilizers to polyvinyl chloride is an effective way to improve its thermal stability. Calcium zinc stabilizers are non-toxic and non-polluting. They can capture hydrogen chloride produced by the decomposition of polyvinyl chloride, inhibit the degradation of polyvinyl chloride, and improve its thermal stability.
[0004] However, the commonly used calcium stearate and stearic acid have poor compatibility with PVC, which results in limited improvement in the thermal stability of the prepared polyvinyl chloride, especially the poor stability under the heat state during processing. Therefore, it is necessary to improve the calcium zinc stabilizer. Summary of the invention
[0005] In order to solve at least one of the above technical problems and develop a method to improve the thermal stability of PVC in a heated state during processing, the present application provides a calcium zinc stabilizer, a preparation method and an application.
[0006] On the one hand, the present application provides a calcium zinc stabilizer, which is prepared by including the following components in parts by weight:
[0007] Calcium salt 25-40 parts;
[0008] 15-25 parts of zinc salt;
[0009] 2-5 parts of attapulgite;
[0010] 0.1-0.4 parts of graphene oxide;
[0011] 5 to 8 parts of antioxidant.
[0012] Optionally, the weight ratio of the calcium salt to the zinc salt is 1.5-1.6:1.
[0013] Optionally, the weight ratio of the attapulgite to graphene oxide is 10 to 14:1.
[0014] Optionally, the calcium salt is calcium stearate, and the zinc salt is zinc stearate.
[0015] Optionally, the particle size of the attapulgite is 0.2 μm to 1 μm.
[0016] Optionally, the graphene oxide has a diameter of 0.01 μm to 15 μm, a thickness of 0.55 nm to 3.85 nm, a layer number of <10, and >99% wt.
[0017] Optionally, the antioxidant is one or more combinations of antioxidant 1010, antioxidant 168, and antioxidant 1076.
[0018] In a second aspect, the present application provides a method for preparing the above-mentioned calcium zinc stabilizer, comprising the following steps:
[0019] S1, mixing attapulgite and graphene oxide, and obtaining a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0020] S2, mixing the calcium salt, the zinc salt and the mixture prepared in S1, adding water, and stirring to obtain a mixed solution;
[0021] S3. Add an antioxidant to the mixed solution prepared in S2, mix well, evaporate to dryness to obtain a calcium zinc stabilizer solid, and grind to obtain a calcium zinc stabilizer.
[0022] Optionally, in S3, grinding is performed until the particle size does not exceed 50 μm to obtain a calcium zinc stabilizer.
[0023] In a third aspect, the present application provides the application of the above calcium zinc stabilizer in the field of PVC preparation technology.
[0024] In summary: the present application adds attapulgite and graphene oxide to the calcium zinc stabilizer, and through the unique rod-like structure of attapulgite, a narrow and long channel can be formed in PVC, and through its own porous structure, the calcium ions, zinc ions, etc. in the calcium zinc stabilizer can move along the surface of the attapulgite and the internal pores, and the graphene oxide is semi-embedded in the porous structure inside the attapulgite, thereby increasing the movement speed of ions on the surface and inside of the attapulgite, so that the calcium ions, zinc ions, etc. in the calcium zinc stabilizer can be quickly distributed in the PVC and quickly capture free radicals, thereby further improving the thermal stability of various parts of the PVC, and the PVC is not easy to precipitate during the processing, resulting in performance being affected. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0027] Calcium salt: Calcium stearate is exemplified.
[0028] Zinc salt: Zinc stearate is exemplified.
[0029] Attapulgite: particle size is 0.2μm~1μm.
[0030] Graphene oxide was purchased from Shenzhen Turing Evolution Technology Co., Ltd.
[0031] The electrochemical deposition involved in the following embodiments of the present application is a prior art, and the following method is used as an example.
[0032] Prepare a precursor solution containing attapulgite and graphene oxide. Pre-disperse these materials in a suitable solvent, such as deionized water or ethanol, and add an appropriate amount of surfactant to prevent particle agglomeration. Add electrolyte (sodium sulfate Na2SO4) to provide sufficient conductive ions to ensure smooth passage of current. The substrate material is glass, and the current density is 200mA / cm 2 , the deposition time is 20min. The substrate is placed in the solution as a working electrode, and a counter electrode (platinum electrode) and a reference electrode (silver / silver chloride electrode) are set at the same time. A constant current is applied using an electrochemical workstation to start the deposition process. After the deposition is completed, the substrate is removed and washed with deionized water to remove the undeposited material, and then dried; a mixture of attapulgite and graphene oxide is obtained. Specific embodiments
[0034] Example 1
[0035] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0036] 2 g of attapulgite and 0.4 g of graphene oxide are mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0037] 25 g of calcium salt, 25 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0038] To the mixed solution prepared above, 5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0039] Example 2
[0040] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0041] 2.5 g of attapulgite and 0.35 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0042] 30 g of calcium salt, 20 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0043] To the mixed solution prepared above, 5.5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size of no more than 50 μm to obtain a calcium zinc stabilizer.
[0044] Example 3
[0045] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0046] 3 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0047] 35 g of calcium salt, 15 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0048] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0049] Example 4
[0050] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0051] 3.5 g of attapulgite and 0.25 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0052] 40 g of calcium salt, 12 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0053] To the mixed solution prepared above, 6.5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0054] Example 5
[0055] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0056] 4 g of attapulgite and 0.2 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0057] 35 g of calcium salt, 15 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0058] To the mixed solution prepared above, 7 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0059] Example 6
[0060] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0061] 4.5 g of attapulgite and 0.15 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0062] 30 g of calcium salt, 20 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0063] To the mixed solution prepared above, 7.5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0064] Example 7
[0065] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0066] 5 g of attapulgite and 0.1 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0067] 25 g of calcium salt, 25 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0068] 8 g of antioxidant was added to the mixed solution prepared above, and after mixing evenly, the mixture was evaporated to dryness to obtain a calcium zinc stabilizer solid, which was ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0069] The calcium zinc stabilizers prepared in Examples 1 to 7 were used to prepare PVC, and the thermal stability performance was tested as follows. The results are shown in Table 1.
[0070] Static test (Congo red method): 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 1.5g calcium zinc stabilizer prepared in Examples 1 to 7, 1g polystyrene particle toughening agent, and 0.3g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing. The mixing temperature was controlled to be 160°C and the mixing time was 10min. After mixing, the sheet was removed to obtain a polyvinyl chloride material.
[0071] Dynamic thermal stability test: 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 2g calcium zinc stabilizer prepared in Examples 1 to 7, 8g hydroxy cross-linked polystyrene particle toughening agent, and 2.2g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing, and the temperature was controlled at 180°C. The color change of the material was recorded at different mixing times. The time when the change occurred was recorded as the dynamic color change time.
[0072] Table 1 Thermal stability test of polyvinyl chloride
[0073]
[0074] It can be seen from the polyvinyl chloride prepared with Examples 1 to 7 and the commercially available calcium zinc stabilizer and Table 1 that when the calcium zinc stabilizer prepared in the present application is used to prepare polyvinyl chloride, the color change time of the prepared polyvinyl chloride in the static test is greatly improved relative to the polyvinyl chloride prepared with the commercially available calcium zinc stabilizer. The color change time of the polyvinyl chloride prepared with the calcium zinc stabilizer of the present application can reach 85 minutes in the static test; the color change time of the polyvinyl chloride prepared with the calcium zinc stabilizer of the present application can reach 92 minutes in the dynamic thermal stability test, which is greatly improved compared with the polyvinyl chloride prepared with the commercially available calcium zinc stabilizer.
[0075] By further analyzing the data in Table 1, it can be seen that the color change time of the polyvinyl chloride corresponding to Examples 2 and 5 can reach more than 90 minutes in the static test, and Examples 3 to 4 can reach more than 100 minutes in the dynamic thermal stability test. The inventor analyzed that this is caused by the relationship between the amount of calcium salt and zinc salt added and the amount of attapulgite and graphene oxide added. Therefore, the inventor further made Examples 8 to 14 to analyze the effect of the weight ratio of the added calcium salt to zinc salt on the performance of the calcium zinc stabilizer.
[0076] Examples 8 to 11 are based on Example 3, without changing the total amount of calcium salt and zinc salt added, and adjusting the weight ratio of calcium salt to zinc salt, as shown below.
[0077] Example 8
[0078] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0079] 3 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0080] 38 g of calcium salt, 12 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0081] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0082] Example 9
[0083] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0084] 3 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0085] 32 g of calcium salt, 18 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0086] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0087] Example 10
[0088] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0089] 3 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0090] 30 g of calcium salt, 20 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0091] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0092] Embodiment 11
[0093] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0094] 3 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0095] 28 g of calcium salt, 22 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0096] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0097] The calcium zinc stabilizers prepared in Examples 1 to 7 were used to prepare PVC, and the thermal stability performance was tested as follows. The results are shown in Table 1.
[0098] Static test (Congo red method): 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 1.5g calcium zinc stabilizer prepared in Examples 1 to 7, 1g polystyrene particle toughening agent, and 0.3g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing. The mixing temperature was controlled to be 160°C and the mixing time was 10min. After mixing, the sheet was removed to obtain a polyvinyl chloride material.
[0099] Dynamic thermal stability test: 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 2g calcium zinc stabilizer prepared in Examples 1 to 7, 8g hydroxy cross-linked polystyrene particle toughening agent, and 2.2g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing, and the temperature was controlled at 180°C. The color change of the material was recorded at different mixing times. The time when the change occurred was recorded as the dynamic color change time.
[0100] Examples 12 to 14 are based on Example 4, without changing the total amount of calcium salt and zinc salt added, and adjusting the weight ratio of calcium salt to zinc salt, as shown below.
[0101] Example 12
[0102] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0103] 3.5 g of attapulgite and 0.25 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0104] 35 g of calcium salt, 17 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0105] To the mixed solution prepared above, 6.5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0106] Embodiment 13
[0107] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0108] 3.5 g of attapulgite and 0.25 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0109] 32 g of calcium salt, 20 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0110] To the mixed solution prepared above, 6.5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0111] Embodiment 14
[0112] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0113] 3.5 g of attapulgite and 0.25 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0114] 30 g of calcium salt, 22 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0115] To the mixed solution prepared above, 6.5 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0116] The calcium zinc stabilizers prepared in Examples 8 to 14 were used to prepare PVC, and the thermal stability performance was tested as follows. The results are shown in Table 2.
[0117] Static test (Congo red method): 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 1.5g calcium zinc stabilizer prepared in Examples 8 to 14, 1g polystyrene particle toughening agent, and 0.3g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing. The mixing temperature was controlled to be 160°C and the mixing time was 10min. After mixing, the sheet was removed to obtain a polyvinyl chloride material.
[0118] Dynamic thermal stability test: 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 2g calcium zinc stabilizer prepared in Examples 8 to 14, 8g hydroxy cross-linked polystyrene particle toughening agent, and 2.2g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing, and the temperature was controlled at 180°C. The color change of the material was recorded at different mixing times. The time when the change occurred was recorded as the dynamic color change time.
[0119] Table 2 Thermal stability test of polyvinyl chloride
[0120]
[0121]
[0122] It can be seen from the polyvinyl chloride prepared in Examples 3 to 4, Examples 8 to 14 and Table 2 that when the weight ratio of calcium salt to zinc salt in the technical solution of the present application is in the range of 1.5 to 1.6:1, the corresponding polyvinyl chloride can change color for more than 90 minutes in a static test, and has good performance.
[0123] Examples 15 to 17 are based on Example 3, without changing the addition amounts of other components in the formula, and adjusting the addition amount of attapulgite, as shown below.
[0124] Embodiment 15
[0125] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0126] 2 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0127] 35 g of calcium salt, 15 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0128] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0129] Example 16
[0130] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0131] 4 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0132] 35 g of calcium salt, 15 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0133] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0134] Embodiment 17
[0135] This embodiment is used to prepare a calcium zinc stabilizer, and the specific preparation method is as follows.
[0136] 5 g of attapulgite and 0.3 g of graphene oxide were mixed to obtain a mixture of attapulgite and graphene oxide by electrochemical deposition;
[0137] 35 g of calcium salt, 15 g of zinc salt and the mixture prepared above were mixed, water was added, and the mixture was stirred to obtain a mixed solution;
[0138] To the mixed solution prepared above, 6 g of antioxidant was added, mixed evenly, evaporated to dryness to obtain a calcium zinc stabilizer solid, and ground to a particle size not exceeding 50 μm to obtain a calcium zinc stabilizer.
[0139] The calcium zinc stabilizers prepared in Examples 15 to 17 were used to prepare PVC, and the thermal stability performance was tested as follows. The results are shown in Table 3.
[0140] Static test (Congo red method): 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 1.5g calcium zinc stabilizer prepared in Examples 15 to 17, 1g polystyrene particle toughening agent, and 0.3g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer and mixed. The mixing temperature was controlled at 160°C and the mixing time was 10min. After mixing, the sheet was removed to obtain a polyvinyl chloride material.
[0141] Dynamic thermal stability test: 100g polyvinyl chloride, 3g plasticizer dioctyl phthalate, 2g calcium zinc stabilizer prepared in Examples 15-17, 8g hydroxy cross-linked polystyrene particle toughening agent, and 2.2g compatibilizer maleic anhydride grafted polyvinyl chloride were added to a double-roll plasticizer for mixing, and the temperature was controlled at 180°C. The color change of the material was recorded at different mixing times. The time when the change occurred was recorded as the dynamic color change time.
[0142] Table 3 Thermal stability test of polyvinyl chloride
[0143]
[0144]
[0145] It can be seen from the polyvinyl chloride prepared corresponding to Examples 3 and 15 to 17 and Table 3 that when the weight ratio of attapulgite to graphene oxide in the technical solution of the present application is in the range of 10 to 14:1, the color change time of the corresponding polyvinyl chloride in the dynamic thermal stability test can reach more than 100 minutes, and the performance is good.
[0146] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A calcium zinc stabilizer, characterized in that The method is prepared by comprising the following components in parts by weight: Calcium salt 25-40 parts; 15-25 parts of zinc salt; 2-5 parts of attapulgite; 0.1-0.4 parts of graphene oxide; 5 to 8 parts of antioxidant.
2. The calcium zinc stabilizer according to claim 1, characterized in that The weight ratio of the calcium salt to the zinc salt is 1.5-1.6:
1.
3. The calcium zinc stabilizer according to claim 1, characterized in that The weight ratio of the attapulgite to graphene oxide is 10 to 14:
1.
4. The calcium zinc stabilizer according to claim 1, characterized in that The calcium salt is calcium stearate, and the zinc salt is zinc stearate.
5. The calcium zinc stabilizer according to claim 1, characterized in that The particle size of the attapulgite is 0.2 μm to 1 μm.
6. The calcium zinc stabilizer according to claim 1, characterized in that The graphene oxide has a diameter of 0.01 μm to 15 μm, a thickness of 0.55 nm to 3.85 nm, a layer number of less than 10, and a weight percentage of more than 99%.
7. The calcium zinc stabilizer according to claim 1, characterized in that The antioxidant is one or more combinations of antioxidant 1010, antioxidant 168, and antioxidant 1076.
8. A method for preparing the calcium zinc stabilizer according to claim 1, characterized in that: The following steps are involved: S1, mixing attapulgite and graphene oxide, and obtaining a mixture of attapulgite and graphene oxide by electrochemical deposition; S2, mixing the calcium salt, the zinc salt and the mixture prepared in S1, adding water, and stirring to obtain a mixed solution; S3. Add an antioxidant to the mixed solution prepared in S2, mix well, evaporate to dryness to obtain a calcium zinc stabilizer solid, and grind to obtain a calcium zinc stabilizer.
9. The preparation method according to claim 8, characterized in that In the S3, grinding is performed until the particle size does not exceed 50 μm to obtain a calcium zinc stabilizer.
10. Use of the calcium zinc stabilizer according to claim 1 in the technical field of PVC preparation.
Citation Information
Cited By
Environment-friendly calcium-zinc stabilizer for PVC (polyvinyl chloride) as well as preparation method and application of calcium-zinc stabilizer
CN122465214A